DNA binding activity of polyoma virus large tumor antigen. - Dilworth, S M (1984)
Polyoma virus large tumor antigen from productively infected mouse cells has been purified to greater than 50% homogeneity by a simple immunoaffinity procedure using monoclonal antibodies. A radioimmunoreaction was devised for assaying purity. The purified large tumor antigen retained its antigenicity and its ability to bind DNA specifically. The regions on the polyoma virus genome recognized by the protein were characterized. Three binding regions were localized within the portion of the genome between the viral origin of DNA replication and the protein coding sequence, overlapping the early promoter and the sites of initiation of mRNAs that specify the viral tumor antigens. The binding regions each contain direct repeats of the pentanucleotide sequence G-R-G-G-C.